Stitched postcards : beautiful textile designs in miniature using quilting and mixed media techniques - Rolf, Christa (Search Press, 2009)
"Postcard-sized works of art, also known as Artist Mailing Cards, one of the latest ideas to emerge from the world of mixed media art"--Back cover.